Worked Over : The Corporate Sabotage of an American Community - Doukas, Dimitra, 1948- (Book collections on Project MUSE., 2003)
"Worked Over is about large-scale social change seen at close range, through the lives of generations of working people in a small manufacturing center [comprising the Mohawk River Valley towns of Herkimer, Ilion, Frankfort, and Mohawk] along New York State's old Erie Canal ... [T]he Remington company, maker of arms and typewriters among other things, was for many years the backbone of a thriving regional society. Corporate takeover of the varied Remington enterprises in 1886 ushered in a century of social distress and decreasing political autonomy. Since the 1970s, the area has suffered mightily from deindustrialization."--Back cover